2019
DOI: 10.21067/jpig.v2i2.3506
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompetensi Pedagogik Dan Kesiapan Guru Terhadap Implementasi Kurikulum 2013

Abstract: Kurikulum merupakan salah satu hal penting dalam sistem pendidikan Indonesia. Permasalahan pendidikan yang dihadapi sekarang membuat Kemendikbud menilai bahwa perlu dikembangkannya kurikulum baru, yaitu Kurikulum 2013. Kompetensi pedagogik merupakan kemampuan guru mengelola pembelajaran yang terdiri dari pemahaman terhadap siswa, perencanaan, implementasi pembelajaran, evaluasi hasil belajar dan mengaktualisasikan segenap potensi siswa. Kesiapan guru merupakan  kesiapan sebagai agen pembelajaran yang berfungsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The t-test showed that only Pedagogical Competence (X1) of Economics Teachers in Bandung Raya has a positive and significant influence on the Effectiveness of Curriculum 2013 Implementation (Y), meaning that the 2013 curriculum implementation will be more effective with the support of better Economics Teacher Pedagogical competence. This finding was in line with the results of Kusufa's research concerning the effect of pedagogical competence and teacher readiness on the Curriculum 2013 implementation which stated that pedagogical competence has a significant influence [8].…”
Section: Discussionsupporting
confidence: 89%
“…The t-test showed that only Pedagogical Competence (X1) of Economics Teachers in Bandung Raya has a positive and significant influence on the Effectiveness of Curriculum 2013 Implementation (Y), meaning that the 2013 curriculum implementation will be more effective with the support of better Economics Teacher Pedagogical competence. This finding was in line with the results of Kusufa's research concerning the effect of pedagogical competence and teacher readiness on the Curriculum 2013 implementation which stated that pedagogical competence has a significant influence [8].…”
Section: Discussionsupporting
confidence: 89%
“…According to Winata, Cacik, & Widiyanti (2018) scientific literacy is knowledge and understanding of scientific concepts and processes for making personal decisions. Science literacy capabilities include the ability to identify problems, collect data and information and also proceed the data obtained and draw conclusions in accordance with the data and information (Huda and Hashim, 2021;Kusufa, 2019).…”
Section: Introductionmentioning
confidence: 99%